Human-robot collaborative disassembly line balancing considering the safe strategy in remanufacturing - Xu, Wenjun; Cui, Jia; Liu, Bin; Liu, Jiayi; Yao, Bitao; Zhou, Zude (Journal of cleaner production, 2021)
Remanufacturing is an important method to realize resource saving and circular economy. Disassembly is a vital step of remanufacturing and it is always finished by manual labor which is low efficiency. Although robotic disassembly covers the shortages of manual disassembly, it is still difficult for the robots to independently finish the disassembly process without the operator's assistance. The human-robot collaborative disassembly is being paid increasing attention and the human-robot collaborative disassembly line balancing is to assign suitable disassembly tasks to each human-robot collaborative disassembly workstation in a balanced manner. In human-robot collaborative disassembly, the operator's safety should be considered when the robot collaboratively executes the disassembly tasks with the operator. In this paper, disassembly information model of human-robot collaborative disassembly considering the safe strategy is studied. After that, this paper solves the human-robot collaborative disassembly line balancing problem using the improved discrete bees algorithm. To verify the proposed method, case study based on a bearing coupler is carried out. The results show the proposed improved discrete bees algorithm can generate the optimal solutions of human-robot collaborative disassembly line balancing problem considering the safe strategy and finds better solutions compared with the other optimization algorithms in terms of running time, average generational distance and Pareto fronts. •Human-Robot collaborative disassembly considers the advantages of both manual disassembly and robotic disassembly.•The safe strategy between the operator and the robots is considered.•An improved discrete Bees algorithm was utilized to generate the optimal solutions of human-robot collaborative disassembly line balancing problems considering safe strategy.